2017
DOI: 10.1007/s00431-017-3043-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effect of low-level laser therapy (LLLT) on chemotherapy-induced oral mucositis in pediatric and young patients

Abstract: Prophylactic LLLT reduces mucositis and severe mucositis and decreases the average severity of oral mucositis in pediatric and young patients with cancer. Therapeutic LLLT also reduces the average severity of oral mucositis and oral pain. Further research should investigate the optimal parameter of LLLT in pediatric and young patients, and studies with higher methodological quality should be performed. What is known: • Low-level laser therapy (LLLT) was recommended by Multinational Association of Supportive Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 31 publications
5
69
0
14
Order By: Relevance
“…Sung et al in their study concluded LLLT is effective in reducing severe mucositis in patients receiving treatment for cancer and undergoing HSCT, although methodological concerns and potential publication bias may mean that the treatment effects observed in these trials are exaggerated . He et al performed a systematic review and meta‐analysis of the effect of LLLT on chemotherapy‐induced OM in pediatric and young patients and reported that the prevalence and severity of grade III OM or worse were statistically significantly lower compared with the placebo . According to the guidelines of the Multinational Association of Supportive Care in Cancer and the International Society for Oral Oncology, laser treatment can be used as a supportive treatment for OM caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al in their study concluded LLLT is effective in reducing severe mucositis in patients receiving treatment for cancer and undergoing HSCT, although methodological concerns and potential publication bias may mean that the treatment effects observed in these trials are exaggerated . He et al performed a systematic review and meta‐analysis of the effect of LLLT on chemotherapy‐induced OM in pediatric and young patients and reported that the prevalence and severity of grade III OM or worse were statistically significantly lower compared with the placebo . According to the guidelines of the Multinational Association of Supportive Care in Cancer and the International Society for Oral Oncology, laser treatment can be used as a supportive treatment for OM caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The Multinational Association of Supportive Care in Cancer and the International Society of Oral Oncology have reported the efficacy of LLLT for prevention of chemotherapy‐induced oral mucositis . Therapeutic LLLT used to treat oral mucositis induced by chemotherapy also demonstrated positive results . Importantly, the American Academy of Pediatric Dentistry recognizes the use of laser as beneficial for the treatment of infants and children, providing pain relief and reducing inflammation associated with ulcers and herpetic lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the American Academy of Pediatric Dentistry recognizes the use of laser as beneficial for the treatment of infants and children, providing pain relief and reducing inflammation associated with ulcers and herpetic lesions . Furthermore, a systematic review and meta‐analysis of the effect of LLLT in pediatric and young patients revealed reductions in the severity of oral mucositis and pain . Moreover, a double‐blind randomized clinical trial demonstrated the efficacy of LLLT in reducing oral mucositis‐associated pain in children, whereas no significant benefit in reduction of the oral mucositis score was verified .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations